O cotidiano, a qualidade de vida e a sobrecarga de cuidadores de idosos em processo demencial de uma unidade escola ambulatorial - Bauab, Juliana Pedroso (2013)
As the number of elderly increases due to the aging population, the prevalence of chronic diseases increases significantly and, among these, dementia stands out being a risk factor for disability and functional loss, promoting a relationship of increased assistance personal care. The progressive deterioration in cognitive and functional evolution of dementia care implies that can be reversed in growing burden of direct family and formal caregivers. This project aims to capture the general perception of formal and informal caregiver forward to their daily lives, overload and its quality of life, and specifically identify the occupations / activities that kept the caregiver and left after taking care of the relationships as well as establish possible correlations with quality of life and care in overhead rates. To this end, we selected a sample of 22 caregivers of patients with dementia diagnostic process, treated at a health facility in the city of São Carlos. These elderly caregivers were contacted 6 and 16 formal caregivers. For data collection where the following instruments were applied: Characterization Questionnaire caregiver, Occupations List, Disability Assessment Scale for Dementia - DAD, and WHOQOL Abbreviated and Scale Zarit Burden Interview. For data analysis descriptive statistical analysis was performed for each variable. From the data collected can be proved in this study that there is an abandonment of daily activities by these carers in productive activities, leisure and self care, and changes in quality of life and levels of overhead, observing differences between formal and informal caregivers.